2023
DOI: 10.3389/fpubh.2022.1082587
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity patterns in South Africa: A latent class analysis

Abstract: IntroductionSouth Africa has the largest burden of HIV worldwide and has a growing burden of non-communicable diseases; the combination of which may lead to diseases clustering in ways that are not seen in other regions. This study sought to identify common disease classes and sociodemographic and lifestyle factors associated with each disease class.MethodsData were analyzed from the South African Demographic and Health Survey 2016. A latent class analysis (LCA) was conducted using nine disease conditions. Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We identified five common co-occurring disease classes: anaemia and hypertension (33.4%), HIV and anaemia (33.2%), HIV and hypertension (19.0%), hypertension and heart disease (7.8%), and diabetes and hypertension (6.6%). Similar latent classes were identified in a study that included all people over the age of 15 years also using the SADHS 2016 (e.g., (1) HIV, hypertension and anaemia (39.4%), (2) anaemia and hypertension (23.7%), (3) cardiovascular-related (19.9%), and (4) diabetes and hypertension (17.0%)) [32], indicating that these diseases could start clustering together at fairly young ages in individuals. However, longitudinal studies may be more useful in determining the age of onset for these diseases.…”
Section: Discussionsupporting
confidence: 53%
“…We identified five common co-occurring disease classes: anaemia and hypertension (33.4%), HIV and anaemia (33.2%), HIV and hypertension (19.0%), hypertension and heart disease (7.8%), and diabetes and hypertension (6.6%). Similar latent classes were identified in a study that included all people over the age of 15 years also using the SADHS 2016 (e.g., (1) HIV, hypertension and anaemia (39.4%), (2) anaemia and hypertension (23.7%), (3) cardiovascular-related (19.9%), and (4) diabetes and hypertension (17.0%)) [32], indicating that these diseases could start clustering together at fairly young ages in individuals. However, longitudinal studies may be more useful in determining the age of onset for these diseases.…”
Section: Discussionsupporting
confidence: 53%
“…Results of these studies combined highlight the hey role of hypertension in driving multimorbidity in the SA population and calls for the need for hypertension to be addressed in the country. 56 Collectively, these results illustrate the complex interactions between infectious diseases like HIV and other chronic health conditions. The heterogeneous epidemiological landscapes in SA could be shaped by communities suffering distinct epidemics, possibly driven by the uneven distribution of health and socioeconomic determinants that fueled the infectious and NCDs epidemics at different intensities between regions in the country.…”
Section: Discussionmentioning
confidence: 92%
“…South Africa is currently experiencing a convergence of NCDs and CDs [ 22 , 23 , 24 , 25 , 26 ], causing the burden of multimorbidity to range from 3% to 87% in various group populations. The common multimorbidity patterns in South Africa are combined TB and HIV, hypertension and diabetes, and hypertension and HIV [ 27 ], and to a lesser extent, the coexistence of HIV, anaemia hypertension, and/or diabetes has been reported [ 28 ]. Although South Africa has put in place a primary health care approach for a better health care since the inception of the democratic government in 1994 [ 29 , 30 ], the country remains burdened with NCDs and CDs coexisting [ 13 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although South Africa has put in place a primary health care approach for a better health care since the inception of the democratic government in 1994 [ 29 , 30 ], the country remains burdened with NCDs and CDs coexisting [ 13 , 23 , 25 ]. Despite the increasing co-occurrence of multiple chronic conditions and poor clinical outcomes among chronic patients [ 13 ], minimal research has been conducted on multimorbidity in South Africa [ 27 , 28 ]. While multimorbidity requires a complexity of care [ 13 , 31 , 32 ], most local studies have reported medication adherence from a single index point of view for hypertension, diabetes, and HIV treatments.…”
Section: Introductionmentioning
confidence: 99%